1970
DOI: 10.13057/nusbiosci/n080112
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal population on various cropping systems on sandy soil in dryland area of North Lombok, Indonesia

Abstract: Abstract. Astiko W, Fauzi MT, Sukartono. 2016. Mycorrhizal population on various cropping systems on sandy soil in dryland area of North Lombok,. Inoculation of arbuscular mycorrhizal fungi (AMF) on maize in sandy soil is expected to have positive implications for the improvement of AMF population and nutrient uptake. However, how many increases in the AMF population and nutrient uptake in the second cycle of a certain cropping system commonly cultivated by the farmers after growing their corn crop have not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
2
0
2
Order By: Relevance
“…On the other hand, treatment without mycorrhizal biofertilizer and without adding nutrients (M 0 U 0 ) gave the lowest weight of wet biomass. This is in line with a study that reported that the application of arbuscular mycorrhizal biofertilizer increased the wet weight of the biomass per plot by 150% compared to without the application of mycorrhizal biofertilizer [22]. AMF can increase plant growth and development through a symbiotic mutualism between AMF (at plant roots) and the plant itself.…”
Section: Wet and Dry Weight Of Biomasssupporting
confidence: 91%
“…On the other hand, treatment without mycorrhizal biofertilizer and without adding nutrients (M 0 U 0 ) gave the lowest weight of wet biomass. This is in line with a study that reported that the application of arbuscular mycorrhizal biofertilizer increased the wet weight of the biomass per plot by 150% compared to without the application of mycorrhizal biofertilizer [22]. AMF can increase plant growth and development through a symbiotic mutualism between AMF (at plant roots) and the plant itself.…”
Section: Wet and Dry Weight Of Biomasssupporting
confidence: 91%
“…Fulfillment of macro elements such as N, P and K with chemical fertilization or addition of organic matter can improve the optimization of growth and production of sorghum in ex-tin mining sites of Bangka. The study of sorghum showed that the addition of N, P, K and Ca fertilizers can increase the growth of sorghum dried crops [1]. The giving top dose soil and 20% oganic ingredients provide the best growth for forestry crops in sand tailings [14].…”
Section: Resultsmentioning
confidence: 99%
“…The first phase, rhizosphere collection of Chromolaena odorata, Melastoma affine and Spathoglottis plicata at coordinated of 2 O 31'57.6 "S and 121 O 22'50.7" E, Sorowako, Indonesia. The rhizosphere collection method uses a diagonal system (Subramani, 2009;Astiko et al, 2016).…”
Section: Methodsmentioning
confidence: 99%